Unilateral vocal cord paresis following excision of a large esophageal duplication cyst via median sternotomy in a neonate - Ioannis Georgopoulos; Eleftheria Mavrigiannaki; Nikolaos Christopoulos; Antonios Kourtesis (Elsevier, 2021)
A newborn, prenatally diagnosed with a cystic mass, possible esophageal duplication cyst, of the upper posterior mediastinum was admitted to our department with symptoms of worsening respiratory distress. A median sternotomy and complete cyst resection were performed, yet worsening respiratory distress was a major concern in the immediate postoperative period which led to further hospitalization and investigations.Surgical resection is the gold standard in therapy for esophageal duplication cysts as reported by all authors that have published such cases. Resection is considered the safest approach to prevent a patient from complications such as hemorrhage, infection, perforation and malignant transformation, yet very few data are published regarding operative complications and pitfalls.